2022
DOI: 10.3390/ijerph191710586
|View full text |Cite
|
Sign up to set email alerts
|

Psychopathological Impact in Patients with History of Rheumatic Fever with or without Sydenham’s Chorea: A Multicenter Prospective Study

Abstract: Sydenham’s chorea (SC) is a post-streptococcal autoimmune disorder of the central nervous system, and it is a major criterium for the diagnosis of acute rheumatic fever (ARF). SC typically improves in 12–15 weeks, but patients can be affected for years by persistence and recurrencies of both neurological and neuropsychiatric symptoms. We enrolled 48 patients with a previous diagnosis of ARF, with or without SC, in a national multicenter prospective study, to evaluate the presence of neuropsychiatric symptoms s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 39 publications
0
0
0
Order By: Relevance
“…In Sydenham's chorea [92], immunomodulatory therapy did not seem to change the short-term outcome compared with symptomatic therapy alone (i.e., antiepileptics and antipsychotics); nevertheless, individuals without immunomodulatory therapy seemed to have a higher relapse rate [59]. One study demonstrated short-term benefits of HD-IVIG, but data on long-term neurological and psychiatric outcomes were not available [60,61].…”
Section: Other Neurological Disorders With Limited or Inconclusive Ev...mentioning
confidence: 99%
“…In Sydenham's chorea [92], immunomodulatory therapy did not seem to change the short-term outcome compared with symptomatic therapy alone (i.e., antiepileptics and antipsychotics); nevertheless, individuals without immunomodulatory therapy seemed to have a higher relapse rate [59]. One study demonstrated short-term benefits of HD-IVIG, but data on long-term neurological and psychiatric outcomes were not available [60,61].…”
Section: Other Neurological Disorders With Limited or Inconclusive Ev...mentioning
confidence: 99%